Fluconazole Resistance and Heteroresistance in Cryptococcus spp.: Mechanisms and Implications - Izabela de Mesquita Bárcia Moreira; Naira Sulany Oliveira de Sousa; Juan Diego Ribeiro de Almeida; Robert Langlady Lira Rosas Filho; Katia Santana Cruz; Ani Beatriz Jackisch Matsuura; Márcia de Souza Carvalho Melhem; Érica Simplício de Souza; Hagen Frickmann; Marcus Vinícius Guimarães Lacerda; João Vicente Braga de Souza (Revista da Sociedade Brasileira de Medicina Tropical)
ABSTRACT The reference methodology for evaluating antifungal susceptibility is based on determining the minimum inhibitory concentration (MIC), which is the lowest drug concentration capable of inhibiting fungal growth. However, such MIC data are insufficient to measure antifungal susceptibility if a strain is heteroresistant to the tested drug. In such cases, a minority subpopulation of fungal cells, originating from an initially susceptible lineage, can grow at antifungal drug concentrations above the MIC. In studies on fluconazole heteroresistance in Cryptococcus spp., chromosomal disomy has been shown to result in the overexpression of two genes located on chromosome 1 (Chr1) linked to antifungal resistance: ERG11 and AFR1. This review addresses the underlying mechanisms of antifungal resistance, the evolution of methods for determining antifungal susceptibility, and the clinical implications of Cryptococcus heteroresistance to fluconazole. The analysis of the findings indicated a correlation between heteroresistance and adverse clinical outcomes, although this observation still lacks definite confirmation in the literature. This highlights the need to implement more efficient therapeutic strategies and improve antifungal susceptibility and heteroresistance testing.